KEABSAHAN PERKAWINAN SEDARAH MASYARAKAT ADAT BATAK TOBA MENURUT HUKUM ADAT - Aktor Pimadona; Mulati Mulati (Fakultas Hukum Universitas Tarumanagara, 2019)
Marriage is a sacred activity because it relates to the religion and beliefs of each. The Batak Toba community is one of all tribes in Indonesia that adhere to their customs and customs, but lately there has emerged the phenomenon of blood marriages in the Batak Toba indigenous people because they feel like each other without thinking about the sanctions that will be received later. In this study, the issue was raised about how legitimacy of the blood marriage of the Batak Toba indigenous people according to customary law? The author examines the problem using normative methods. The results showed that the marriage of the Batak Toba community was not in accordance with the rules applicable in customary law, because the marriage system of the Batak Toba indigenous people themselves embraced an exogamous marriage system in which the Batak Toba indigenous people could marry the man or woman they liked must be outside the clan or the clan itself. Then in this study there are also ways to preserve the culture of the Batak Toba indigenous people who are increasingly disappearing because of the modern era that exists today.